The Complexities of Implementing Election Systems in Indonesia - Sulaiman, King Faisal; Fitrantyo, Zidan Risqy (Media of Law and Sharia, 2025)
Indonesia's electoral framework has undergone significant transformations since the nation's first democratic experiment in 1955. While the open-list proportional system currently employed seeks to empower voters and enhance representational legitimacy, it has also engendered unintended consequences, including heightened campaign expenditures, weakened party institutionalization, and electoral fatigue among officials. Conversely, the closed-list proportional system, though more cost-efficient and conducive to party discipline, is often criticized for diminishing direct voter influence and fostering elitist candidate selection. This article critically examines the paradoxes inherent in both systems through doctrinal and historical legal analysis, supported by empirical data from the 2014 and 2019 general elections. The findings reveal that Indonesia’s electoral challenges lie not merely in the choice between open and closed systems but in the institutional mechanisms that mediate electoral participation, candidate selection, and political financing. The paper proposes an integrative model that balances voter agency, political accountability, and electoral integrity, while recommending reforms inspired by comparative practices such as intra-party primaries and digital voting innovations. These insights are aimed at strengthening Indonesia’s democratic resilience within the bounds of its constitutional framework.